Assessment of freshwater plant diversity and local difference in freshwater plant use knowledge in Punakha district, Bhutan - Dema, Tenzin; Pem, Tshering; Jambay; Tshomo, Sangay; Tshering, Sonam (International Journal of Environment, 2022)
Freshwater plants play a paramount role in an aquatic ecosystem. However, only limited studies have been carried out on freshwater plants. Therefore, the study aimed to assess the diversity of freshwater plants in different freshwater bodies of Punakha District, the correlation of freshwater plant species with the environmental variables, and the local community difference in freshwater plant use knowledge in Punakha district. A total of 20 water bodies were selected using a stratified sampling method. Area-based surveys were employed to assess the plant species from a total of 80 plots, each with the quadrat of 5 m x 5 m. Environmental variables such as altitude, water depth, water velocity, temperature, precipitation and evapotranspiration were measured. The study recorded a total of 72 freshwater plant species distributed among 57 genera and 37 families. Shannon-Weiner diversity index revealed high diversity of freshwater plants from ponds (H’ = 3.3) followed by ditches (H’ = 3.16), streams (H’ = 3.07) and lakes (H’ = 2.83). The study revealed the decrease of freshwater plant species with an increase in the water velocity, depth and altitude. There was a significant association between respondents’ freshwater plant use knowledge with gender (x2 (1) = 6.04, p = .014), age (x2 (1) = 13.21, p = .000) and education level (x2 (1) = 4.53, p = .003). Females and illiterate respondents with aged 31 years old and above had more knowledge on freshwater plant use compared to males and educated respondents with aged 30 years old and below.